Potensi Biofisik Kawasan Konservasi sebagai Dasar Pengembangan Ekowisata Daerah Kabupaten Pesisir Selatan (Studi Kasus: Lubuk Larangan Bendung Sakti Inderapura) - Ira Desmiati; Siti Aisyah (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Currently Lubuk Larangan Bendung Sakti is expected to be gradually becoming an attractive tourist destination. There are several activities that can be done in ecotourism Lubuk Larangan Bendung Sakti which has the potential to become an ecotourism place. The purpose of this study is to examine how the development of ecotourism in Lubuk Larangan Bendung Sakti is assessed from A3 (Attractions, Accessibility, and Amenities) and biophysically the water quality of Lubuk Larangan Bendung Sakti waters in Pesisir Selatan Regency. The method used is descriptive quantitative with a score rating and followed by a water quality test using the STORET test. The results of the study indicate that the Biophysics viewed from the aspect of Attractions, Accessibility and Amenity in the Lubuk Larangan Bendung Sakti waters area belongs to the "Good" biophysical condition interval. The water quality condition based on the results of the STORET test shows that the status of the water quality in the "Lubuk Ban" waters area meets the water quality threshold (not polluted) with a score of 0. This shows the status of water quality in Lubuk Larangan Bendung Sakti is in the very good category and is classified in class A, which meets the quality standards. These biophysical conditions indicate that the area of Lubuk Larangan Bendung Sakti is feasible and has the opportunity to be used as an ecotourism area in a sustainable manner.